Kurikulum Tersembunyi Lingkungan di dalam Materi Energi Terbarukan untuk Fisika SMA - Desnita Desnita (Universitas Negeri Jakarta, 2015)
Abstract Renewable energy resources education, in essence, is the treatment of various topics and issues related to enewable energy resources and technologies as an environmental hidden curriculum in physics education at Senior High School. Based on the statement, environmental Hidden Curriculum in teaching physics concept, especially renewable energy resource was developed. Used research and development method, with step: need assessment, development theoretic models, validation, trial, and revision. The development result is a curriculum with contain: concept of green energy renewal resource and waste cooking oil as a kind of the resources, producing process, and learning strategies to implementation the curriculum. Implementation as trial this curriculum was conducted at a senior high school in South of Jakarta. Didactic exploration improves the learning process, link or integration in physics concept, when worksheets were used in the physics lab and multimedia system. The worksheet content are picture, video, and text or article about green renewable energy resources. Used project based learning and cooperative learning, using the worksheet was improve not only cognitive aspect of the student, but also their skill and attitude to save environmental. Kata-kata Kunci: environmental hidden curricullum, green renewable energy resources, learning strategies. Abstrak Inti dari pendidikan tentang sumber energi terbarukan adalah ujicoba terhadap sejumlah topik dan isu yang terkait dengan sumber energi terbarukan ramah lingkungan dan teknologinya sebagai sebuah kurikulum tersembunyi dalam pendidikan fisika pada tingkat SMA. Berdasarkan alasan tersebut, telah dikembangkan kurikulum lingkungan yang tersembunyi di dalam mengajar konsep fisika, khususnya sumber energi ramah lingkungan. Hasil pengembangan adalah kurikulum yang berisi konsep sumber energi terbarukan ramah lingkungan dan minyak jelanta sebagai salah satu jenisnya, proses produksi, dan strategi pembelajaran dalam penerapan kurikulum tersebut. Implementasi terhadap siswa salah satu SMA di Jakarta Selatan menunjukkan bahwa materi pembelajaran lingkungan dikaitkan atau diajarkan secara terintegrasi dalam pembelajaran fisika, menggunakan lembar kerja yang berisi konsep, gambar, video, dan teks atau artikel tentang sumber energi terbarukan ramah lingkungan di laboratorium multimedia fisika. Menggunakan pembelajaran berbasis projek dan kooperatif, penggunaan lembar kerja tersebut terbukti meningkatkan tidak hanya pengetahuan, tapi juga keterampilan, dan sikap kepedulian siswa terhadap lingkungan. Kata-kata Kunci: kurikulum lingkungan yang tersembunyi, sumber energi terbarukan ramah lingkungan, strategi pembelajaran